Development of Social Arithmetic Teaching Materials with Islamic Characters on 7th Grader Students - Ega Gradini; Siti Rahma Mulyani; Asnawi Asnawi (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2021)
This study aims to develop Social Arithmetic teaching materials integrated with Islamic characters that valid, practical, and effective. This research is developmental research that deploys afour-D development model from Thiagarajan, Semmel, and Semmel. The research stages are Define, Design, Develop, and Disseminate. The research instruments used were expert validation sheets, teacher and student response questionnaires, and learning outcomes tests. The data analysis of the validity and practicality of the prototype was carried out by converting quantitative data in the form of an assessment score into qualitative data. Effectiveness data analysis was carried out by determining the percentage of student learning completeness based on a standard of learning completeness criteria (KKM).This developmental research produced teaching materials for 7th grader students: Teacher handbooks, Student handbooks, Student Activity Sheets, and Learning Outcomes Tests that integrated with Islamic value; religion, honesty, curiosity, caring, hard work, independence, patience, honest, thoughtful, consistent, and tolerance. The research showed that the developed teaching materials were valid, practical, and effective in Social Arithmetics learning. Teaching materials are declared valid with the content validity value of the Teacher handbook is 1.00; Student handbook is 0.96, and Students Work Sheet is 0.86. Teaching materials are stated to be practical by obtaining an average value of the teacher's response is 4.75, and student response is 3.45 with both categories are good. Teaching materials are declared effective based on the 95% completeness of student mastery learning and hypotheses testingÂ